THE SCIENTIFIC STUDY OF UREA FERTILIZER AND COW MANURE COMPOSITION ON THE GROWTH AND YIELD OF KAILAN PLANTS - Santosa, Sartono Joko; Priyono (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
There are determining factors in agricultural cultivation technologies that significantly affect plant development and productivity. Fertilization is one of the determining factors in agriculture. This research examines the composition of urea fertilizer and cow manure on kalian growth and yield. This research was conducted from 5 October 2021 to 30 November 2021 in Tunggulrejo Village, Jumapolo, Karanganyar, at an altitude of 700 meters above sea level with red latosol soil. This research used a single-factor Complete Randomized Block Design (RAKL) which consisted of 6 trials, and each was repeated four times to obtain 24 problems. The observational data were analysed using an F test with an error level of 5%. The treatment was continued with the DMRT (Duncan's Multiple Range Test) at an error level of 5% when there was an effect during the treatment. The variables used were plant height, number of leaves, leaf area, fresh plant weight, fresh crown weight, dry crown weight, fresh root weight, and dry root weight. The results of the research indicated that the composition of urea fertilizer and the application of cow manure had a significant effect on the growth of leaves of kalian plants; the best and highest number of leaves was 8 (F): Urea 0% + 100% cow manure per plot while the other parameters did not affect plants.